2016
DOI: 10.1021/jacs.6b10227
|View full text |Cite|
|
Sign up to set email alerts
|

All-Inorganic Perovskite Solar Cells

Abstract: The research field on perovskite solar cells (PSCs) is seeing frequent record breaking in the power conversion efficiency (PCE). However, organic-inorganic hybrid halide perovskites and organic additives in common hole-transport materials (HTMs) exhibit poor stability against moisture and heat. Here we report the successful fabrication of all-inorganic PSCs without any labile or expensive organic components. The entire fabrication process can be operated in ambient environment without humidity control (e.g., a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
714
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 951 publications
(761 citation statements)
references
References 33 publications
27
714
0
3
Order By: Relevance
“…Recently, Liang et al [82] reported all-inorganic PVSK solar cells based on CsPbBr 3 electrode. Without the use of any labile or expensive organic components, the cells can be fabricated in ambient environment, thus removing the need for a glovebox.…”
Section: Mixed Cations Based On Ma Fa Cs and Rbmentioning
confidence: 99%
“…Recently, Liang et al [82] reported all-inorganic PVSK solar cells based on CsPbBr 3 electrode. Without the use of any labile or expensive organic components, the cells can be fabricated in ambient environment, thus removing the need for a glovebox.…”
Section: Mixed Cations Based On Ma Fa Cs and Rbmentioning
confidence: 99%
“…In the first step, the effect of the PbBr 2 ·DMF adduct is considered to be important for the formation of CsPb 2 Br 5 . Without the existence of the adduct, the reaction process should be different [19,26]. FT-IR was conducted to confirm the existence of the adduct.…”
Section: Characterizationmentioning
confidence: 99%
“…In 2015, the first inorganic CsPbBr 3 perovskite solar cells (PSCs) were reported by Kulbak et al [17], acquiring a PCE of about 5%. More recently, Liao et al [18] reported CsPbX 3 nanowires stable solar cells with PCE of 1.21% and stability around 5500 h. Liang et al [19] reported carbon-based CsPbBr 3 solar cells with a PCE of 6.7% and stability over three months in humid air (90%-95% relative humidity, 25°C). As for CsPbI 3 , undesired orthorhombic phase was formed with a low PCE of 0.09% due to its poor phase stability to moisture [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the works mentioned above displayed the high stability for solar devices, the structures still contained organic HTM. Jin et al reported the design of all-inorganic perovskite solar cell devices, in which the organic HTM and metal electrode were completely eliminated and a layer of carbon electrode was coated on the CsPbBr 3 layer [51]. The entire fabrication process of the all-inorganic PSCs can be operated in ambient environment without humidity control.…”
Section: Mixed A-site Cationsmentioning
confidence: 99%